Blood Scattering Model for Pulsed Doppler - KARWAT, Piotr; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2009)
The subject of this paper is a new software simulating ultrasound signal scattered on moving blood cells during Doppler examination of blood flow velocity using pulsed technique. Generated data are used for optimization and validation of Doppler signals processing algorithms. The algorithm is based on the finite elements method FEM. A rigorous set of postulates which simplifies physics of modeled phenomenon enables to quicken the program significantly while preserving important properties (from application point of view) of generated signal. The paper includes description of Doppler RF signal generation algorithm. The simplifying postulates are listed together with resulting signal fidelity degradation. Finally generated raw data is presented together with its Doppler Audio and Color processed version. The signal processing results enable to reconstruct correctly the velocity profile and its time dependence. The results clearly confirm that the data generated by the algorithm are suitable for Doppler signals processing.